THE EFFECTIVENESS OF DUOLINGO AS TECHNOLOGY-BASED INSTRUCTIONAL MEDIA IN LEARNING ENGLISH SPEAKING - Kusuma, Dewi Indah; Rahmania, Iftia; Imannisa, Citra; Hentasmaka, Daning (STKIP PGRI Jombang, 2024)
This study aimed to determine the effectiveness of the Duolingo application as technology-based instructional media in learning English speaking especially, in the four speaking aspects. It implemented experimental research with a pre-experimental design. The participants of this study were 25 students enrolled in the eleventh grade at a State Senior High School in Jombang, East Java, Indonesia. Speaking tests in the form of paired dialogue were used to measure students' speaking skill before and after learning English using Duolingo. The data analysis using Wilcoxon Signed Rank Test was used to answer the research questions. The results showed that there was a significant difference in students' speaking skills before and after learning by using Duolingo as technology-based instructional media. Further, this study also revealed that using Duolingo in learning speaking was effective in every aspect – fluency, accuracy, pronunciation, and vocabulary. It is suggested for teachers to use Duolingo as an alternative app for out-of-class learning to enhance students' speaking skills.